A Handheld Technology for Optical Monitoring of Transcutaneous Blood Oxygen Saturation - K.C. Huong, Audrey; E. Ong, P; H. Tsen, V; T. I. Ngu, Xavier (International Journal of Engineering and Technology, 2018)
This paper presents the use of a handheld technology for noninvasive prediction of oneâ€™s transcutaneous blood oxygen saturation, StO2, via an in-house developed skin oxygenation system. The quantification strategy involved the use of wavelength dependent Modified Lambert Beer law and is based on light signals of wavelengths 532 nm, 560 nm and 650 nm reflected from the selected skin site. This study performed at rest and arterial blood occlusion experiment on left palm of the hand of five healthy Asian volunteers to evaluate the performance of the system and to verify the validity of the predicted results. The preliminary results revealed a considerable decrease in the predicted mean percent StO2 value from 63.7 Â± 13.2 % for at rest condition to 52.2 Â± 11.4 % after a pressure of 140 mmHg was applied on upper left arm of these recruits for 120 seconds. This work concluded that the developed optical system is able to provide comprehensive information on spatially dependent StO2 and it has unlimited skin access, hence may be potentially used in field applications to assess the skin oxygen level of those in workforce whose job is at risk of exposure to poisonous gases.Â